Communicable Diseases Intelligence volume 22 issue 5 - May 1998-whole issue - No authors listed, (Communicable Diseases Intelligence, 1998)
Disclaimer: This whole-issue PDF contains one or more 'Policy and Guidelines' items on p. 75, as originally published. The views expressed in each such item are those of the individual authors, and do not necessarily represent the views of the Communicable Diseases Intelligence journal or the Australian Centre for Disease Control. While each 'Policy and Guidelines' item was drafted with consideration to the then-available information on the condition(s) addressed within, it may not be complete and may not represent the currently understood best practice for the referenced condition(s). Readers are advised to refer to the most recent guidance on this matter, where such guidance exists and where its authoritativeness can be established. The guidelines contained within this whole-issue PDF do not replace the need for clinical judgment to be exercised for each individual circumstance, nor the necessity for expert advice to be obtained as appropriate. Contents National Influenza Surveillance 1997 National Health and Medical Research Council (NHMRC) recommendations on influenza vaccination Pertussis in South Australia Japanese encephalitis on the Australian mainland Haemolytic Uraemic Syndrome in South Australia Notice to readers: CDI Internet address Communicable Diseases Surveillance: Highlights (vaccine preventable diseases, arboviruses, hepatitis A, respiratory diseases) National influenza surveillance 1998 (year to date) HIV and AIDS surveillance, reporting period November 1997, assessed as at 28 February 1998 Gonococcal surveillance, reporting period 1 July to 30 September 1997 Sentinel chicken surveillance program, reporting period March 1998 Serious adverse events following vaccination surveillance scheme, reporting period 16 December 1997 to 27 April 1998 National Notifiable Diseases Surveillance System tables, 1 to 28 April 1998 Laboratory Serology and Virology Reporting Scheme tables, 26 March to 22 April 1998 Australian Sentinel Practice Research Network report tables, weeks 13 to 16, 1998 Overseas briefs (dengue and dengue haemorrhagic fever, diarrhoea, meningitis)